Antifungal effects of Eurycoma longifolia jack (Tongkat Ali) root extract against oral Candida albicans - Faisal, Ghasak Ghazi; Arzmi, Mohd Hafiz; Alloha, Irani; Aziz, Nurul ‘Ain Liyana; Abllah, Zurainie (Faculty of Dentistry, University of Malaya, 2018)
Abstract: Eurycoma longifolia jack (E.L) is a herbal medicinal plant of South-East Asian origin, popularly recognized as ‘Tongkat Ali.’ The plant roots have been scientifically proven to have many biological effects.This study was done to determine the antifungal activities of E.L. root extract against Candida albicans. E.L root was extracted using soxhlet method. Disc diffusion assay was conducted using extract concentration of 200mg/ml. Nystatin was used as positive control. Minimum Inhibitory Concentration (MIC) was done to determine the lowest inhibitory concentration of the extract on the microorganism. E.L extract inhibited the growth of Candida albicans at a concentration of 200mg/ml with a zone of inhibition of 16.0 ± 3.0mm . The MIC of E.L extract against Candida albicans was 25mg/ml. The results from this study revealed the potential use of Eurycoma longifolia jack as an antifungal agent which can be used to produce new oral care products.